2017
DOI: 10.1038/s41598-017-05248-6
|View full text |Cite
|
Sign up to set email alerts
|

Ta2O5-TiO2 Composite Charge-trapping Dielectric for the Application of the Nonvolatile Memory

Abstract: The charge-trapping memory devices with a structure Pt/Al2O3/(Ta2O5)x(TiO2)1−x/Al2O3/p-Si (x = 0.9, 0.75, 0.5, 0.25) were fabricated by using rf-sputtering and atomic layer deposition techniques. A special band alignment between (Ta2O5)x(TiO2)1−x and Si substrate was designed to enhance the memory performance by controlling the composition and dielectric constant of the charge-trapping layer and reducing the difference of the potentials at the bottom of the conduction band between (Ta2O5)x(TiO2)1−x and Si subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…With this aim, we will take advantage of our previous studies on the photoelectrochemical characterization of anodic oxide films grown on pure transition metals (TMs) and mixed Al-TM (TM = Nb, Ta, W, Ti, etc.) alloys playing an important role in passivity studies ,,,, as well as in microelectronics , and near-infrared interferometry equipment …”
Section: Modeling the Optical Band Gap Of Ternary Oxide Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…With this aim, we will take advantage of our previous studies on the photoelectrochemical characterization of anodic oxide films grown on pure transition metals (TMs) and mixed Al-TM (TM = Nb, Ta, W, Ti, etc.) alloys playing an important role in passivity studies ,,,, as well as in microelectronics , and near-infrared interferometry equipment …”
Section: Modeling the Optical Band Gap Of Ternary Oxide Systemsmentioning
confidence: 99%
“…With this aim, we will take advantage of our previous studies on the photoelectrochemical characterization of anodic oxide films grown on pure transition metals (TMs) and mixed Al-TM (TM = Nb, Ta, W, Ti, etc.) alloys playing an important role in passivity studies 43,66,67,124,125 as well as in microelectronics 4,126 and near-infrared interferometry equipment. 44 In previous works, in the absence of a general semiempirical approach to the modeling of nonregular amorphous ternary systems, we proposed on a purely heuristic basis the fitting of the E g,opt vs x Al data points of amorphous oxides anodically grown on magnetron-sputtered Al-TM alloys based on the use of eq 1 modified as…”
Section: Modeling the Optical Band Gap Of Ternary Oxide Systemsmentioning
confidence: 99%
“…The charge trapping in thin dielectric films has been intensively investigated recently in order to employ this phenomenon in the non-volatile memories as a replacement of the existing floating gate technology [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. The charge trapping memory (CTM) design has a lot in common with the floating gate design.…”
Section: Introductionmentioning
confidence: 99%
“…The charge‐trap OFET derives from the complementary metal‐oxide semiconductor silicon‐oxide‐nitride‐oxide‐silicon (SONOS) memory, which is nowadays the most viable solution to replace the current floating gate‐based technology and to scale the Flash NAND memories beyond the 16 nm node, although its working mechanism including the carrier transportation in organic semiconductor and the transfer characteristics of OFET is not completely consistent with that of SONOS memory. Recently, much efforts have been made to achieve high performance Si‐based charge‐trap memory (CTM) devices through matching the energy‐band alignments between Si and the charge‐trapping dielectric . It was found that at an applied electric field, the lower difference between the conduction‐band minimum of Si and the charge‐trapping dielectrics leads to a larger memory window, a higher programming/erasing speed and a better retention characteristics for the CTM devices.…”
Section: Introductionmentioning
confidence: 99%
“…

speed, serious retention degradation, and instability in air still should be overcome for the charge-trap OFETs. [14][15][16] It was found that at an applied electric field, the lower difference between the conduction-band minimum of Si and the charge-trapping dielectrics leads to a larger memory window, a higher programming/erasing speed and a better retention characteristics for the CTM devices. Recently, much efforts have been made to achieve high performance Si-based chargetrap memory (CTM) devices through matching the energy-band alignments between Si and the charge-trapping dielectric.

…”
mentioning
confidence: 99%